Label-free analytic histology of carotid atherosclerosis by mid-infrared optoacoustic microscopy - Visscher, Mirjam; Pleitez, Miguel A.; Van Gaalen, Kim; Nieuwenhuizen-Bakker, Ingeborg M.; Ntziachristos, Vasilis; Van Soest, Gijs (Photoacoustics, 2022)
Background and aims: Analysis of atherosclerotic plaque composition is a vital tool for unraveling the pathological metabolic processes that contribute to plaque growth. Methods: We visualize the constitution of human carotid plaques by mid-infrared optoacoustic microscopy (MiROM), a method for label-free analytic histology that requires minimal tissue preparation, rapidly yielding large field-of-view en-face images with a resolution of a few micrometers. We imaged endarterectomy specimens (n = 3, 12 sections total) at specific vibrational modes, targeting carbohydrates, lipids and proteins. Additionally, we recorded spectra at selected tissue locations. We identified correlations in the variability in this high-dimensional data set using non-negative matrix factorization (NMF). Results: We visualized high-risk plaque features with molecular assignment. Consistent NMF components relate to different dominant tissue constituents, dominated by lipids, proteins, and cholesterol and carbohydrates respectively. Conclusions: These results introduce MiROM as an innovative, stain-free, analytic histology technology for the biochemical characterization of complex human vascular pathology.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Atherosclerosis; Cholesterol; Mid-infrared optoacoustic microscopy; Pathology; Spectroscopy